Electromigration of cell surface macromolecules in DC electric fields during cell polarization and galvanotaxis. (7th October 2019) - Sarkar, Anyesha; Kobylkevich, Brian M.; Graham, David M.; Messerli, Mark A.
Highlights: Physical model describes macromolecule electromigration in plasma membranes. Steady-state electromigration of tdTomato-GPI is measured, and predicted by model. Model predicts electromigration for surface proteins involved with galvanotaxis. Proteomics enables predictions for all proteins on the surface of a migratory cell. Two proteins required for transepithelial battery electromigrate to opposite poles. Abstract: DC electric fields (EFs) can often induce cellular polarity, and direct migration of cells toward one of the electrical poles. The mechanism(s) by which cells sense weak EFs is not established. We present here a molecular flux model to describe electromigration of plasma membrane macromolecules and compare its predictions to electromigration of a lipid-anchored surface protein, tdTomato-GPI, under different experimental conditions. Gradients of tdTomato-GPI are assembled based on its electrophoretic and electro-osmotic mobilities and collapsed by its own diffusion. The flux model predicts greatest cathodal accumulation for tdTomato-GPI under slightly acidic conditions, and weak cathodal accumulation under alkaline conditions. Predictions by the flux model align closely with measurements of the electromigration of tdTomato-GPI except at pH 6, the only condition examined in which the protein exhibits a net positive surface charge. We use the model to predict the time course and relative steady state concentration difference for asymmetric accumulation of other surface macromolecules based on their physical properties. We also describe a method for identifying the physical properties of the plasma membrane proteins in zebrafish keratocytes, in order to predict likely candidates for the electric field receptor in this model migratory system that exhibits cathodal galvanotaxis, and to predict the asymmetric distribution of proteins in other cell types. We provide a physical basis for predicting the dynamics of electromigration for numerous cell surface macromolecules and provide evidence for supporting the role of electromigration in directing cell polarity, migration and growth in response to weak EFs. Graphical abstract: Image, graphical abstract